Indefatigable Willingness to Accomplish Objectives: The Relationship Between EFL Learners’ Motivation and Autonomy - Fatemeh Khonamri; Khazar Molana; Marzie Danaei; Mohammad Kazemian (Journal of Languages and Language Teaching, 2020)
The common widespread interest in the socio-cultural aspect of language learning among applied linguists has made ESL researchers draw attention to learners' motivation and autonomy in the European and Asian educational circles. The rationale of this study is to pinpoint the relationship between EFL learners’ motivation and autonomy. To gather relevant data, motivation and autonomy questionnaires were distributed among 100 EFL learners, who were chosen through Quick Placement Test (QPT), and were put them into B2, C1, and C2 levels of linguistic proficiency based on Common European Framework Rubric (CEFR) model. To fulfill the objectives of this study, both descriptive and inferential statistics were utilized in the process of data analysis. Regarding the statistical analysis, learners’ motivation significantly correlated with their autonomy. Additionally, it was found that there was a significant positive correlation between autonomy and intrinsic motivation, while the correlation between autonomy and extrinsic motivation was significant but negative. This study can shine a light on language teaching in general and in particular on the relationship between EFL learners' motivation and autonomy.